HTML 4 for dummies - Tittel, Ed.; Pitts-Moultis, Natanya; Valentine, Chelsea, 1972- (Foster City, CA : IDG Books Worldwide, 2000)
1. Hypertext systems. 2. HTML (Document markup language) 3. World wide web
"A reference for the rest of us!"--Cover.
Basic ed. students
Keywords: HTML (Document markup language)